2018
DOI: 10.1038/s41598-018-19249-6
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic topography of the greater and third occipital nerves and its clinical implication

Abstract: This study aimed to provide topographic information of the greater occipital (GON) and third occipital (3ON) nerves, with the three-dimensional locations of their emerging points on the back muscles (60 sides, 30 cadavers) and their spatial relationship with muscle layers, using a 3D digitizer (Microscribe G2X, Immersion Corp, San Jose CA, USA). With reference to the external occipital protuberance (EOP), GON pierced the trapezius at a point 22.6 ± 7.4 mm lateral and 16.3 ± 5.9 mm inferior and the semispinalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In our previous cadaveric study, approximately 30.2 mm horizontal distance from the midline (C2 spinous process), the GON winds around the OCI muscle, then ascends vertically and turns medially at the upper border of this muscle. 14 This finding indicates that the distance between the GON and TON is closest at the superomedial area of the OCI muscle. 14 Therefore, the GON would be most suitable for target at the C2 level on the inferolateral area of the OCI muscle, where it is anatomically farthest away from the TON.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our previous cadaveric study, approximately 30.2 mm horizontal distance from the midline (C2 spinous process), the GON winds around the OCI muscle, then ascends vertically and turns medially at the upper border of this muscle. 14 This finding indicates that the distance between the GON and TON is closest at the superomedial area of the OCI muscle. 14 Therefore, the GON would be most suitable for target at the C2 level on the inferolateral area of the OCI muscle, where it is anatomically farthest away from the TON.…”
Section: Discussionmentioning
confidence: 81%
“…The blocks were performed by a single, experienced anesthesiologist specialized in regional anesthesia and pain medicine. A TE7 ultrasound unit (Mindray Bio-Medical Electronics, Shenzhen, People's Republic of China) with a high-frequency linear probe (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and an 80-mm, 22-gage needle was used in every case. The ultrasound approach in this study follows the previously described method.…”
Section: Ultrasound-guided Gon Block Proceduresmentioning
confidence: 99%
“… 3 It serially passes or pierces the layered back muscles such as the obliquus capitis inferior (on 2.5–3 cm lateral to midline), the semispinalis capitis (on 1–1.5 cm inferior to the SNL and 3 cm lateral to midline), and the trapezius (on 1–1.5 cm inferior to the SNL and 2.5–3.5 cm lateral to midline). 1 , 16 , 17 In the past, previous studies have focused on the emergence of the nerves on the layered back muscles for guiding nerve blocks. However, the detailed distribution of the cutaneous nerve fibers should be examined for diagnosis and treatment of the nerve triggering the pain.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study, where the reference point is external occipital protuberance, TON pierced the SSC at 1.2±1 cm lateral and 6.1±1.5 cm inferior, the splenius capitis at 1±0.5 cm lateral and 5.9±2 cm inferior, and the trapezius at 1.3±0.9 cm lateral and 4.4±2.1 cm inferior. 17 It is well known that this nerve is typically located medial to the GON at the cervico-occipital level. 16 , 17 However, we found that the TON did not appear to extend above the SNL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation